(3GdHDQI (B..(3h OhGFQ GdEJUGd (B:s (3OQGSI aj GdeaGgje GdfbOjI h JWHjbGJgG (B/s - (3GdZjK, fSjeIs ((3GdchjJ (B:s (3OGQ bHGA ddWHGYI h GdfTQ h GdJhRjY ,s, 2000)
(3GdHDQI eUWdM MOGKj egeJg GdcTa Yf GdNdjI GdMGceI dJTcjd GdfU GdCOHj h JhMjO CdhGfg h WHjYJg (B. (3jJee GdEJUGd QSGdI GdHDQI hhXjaJgG MjK JSYi CfG GdeHOY Edi GdCNQ (B.(3Ef GdfGbOI JHOC HLdGA GdeUWdM aj GdHdGZI h GdEJUGd Ke JJGHY JLdjGJg h JeOOg Ydi eSGMI fU SOQj ebGeGJ GdgePGfj h JNWjg Cab GdcJGHI Edi Cab GdeQLYjI CeQD GdbjS aj GdeUGOQ GdHdGZjI SHGMJg YcS JjGQ GdeCdha aj JLQHI GdQKGA YfO GeQCI JJMOi gPg GdOQGSI JDcO Cf GdMOGKI efgL eDUd h djSJ GfWdGbg YUQ jDPf HGdEfJgGAs
(3HjHdjhZQGajG(B:(3U(B.192-196s
Keywords: (3GdEJUGds